Penguasaan konsep aljabar dan aritmatika untuk menyelesaikan soal-soal fisika dasar - Sitti Rahmasari (STKIP PGRI Banjarmasin, 2019)
Mathematics and physics are closely intertwined because mathematical concepts are used in physics. Physics is a part of science that studies natural behavior through experimental observations and quantitative measurements. Physics uses the language of mathematics to model natural phenomena into mathematical equations, so that in studying physics, mathematical abilities are needed as students' initial abilities in solving physics problems. This study uses a quantitative approach with a descriptive correlation method to analyze the mathematical concepts needed to solve the physical problems of the static electricity material in the Antasari Tadris Physics study program. The results of the study show that there is a high correlation between mastery of arithmetic and algebraic concepts with the ability of students to solve basic physics questions.